2002
DOI: 10.1093/ageing/31.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training in the 'oldest old': the effect of 24 weeks of training

Abstract: progressive aerobic training can increase the maximal aerobic power of very elderly women. A 15% increase in VO(2)max may prevent many elderly women from crossing functionally important thresholds, thereby helping to maintain independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 19 publications
2
33
0
4
Order By: Relevance
“…Other studies have reported gender diVerences in response to training (Malbut et al 2002;Aniansson et al 1983;Roth et al 2001). Roth (2001) has shown signiWcant muscle cross-sectional area increases in females over 70 but not in men after a 6-month training.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have reported gender diVerences in response to training (Malbut et al 2002;Aniansson et al 1983;Roth et al 2001). Roth (2001) has shown signiWcant muscle cross-sectional area increases in females over 70 but not in men after a 6-month training.…”
Section: Discussionmentioning
confidence: 93%
“…We have also previously shown that treadmill exercise training in late-middle-aged F344BN rats can restore muscle aerobic function and enzyme activity levels to young adult levels (9). Only a few studies have investigated endurance or resistance exercise training effects in very old humans ('79 yr), and although there are clear benefits to exercise training (22), overall these studies suggest that in very old age (20,41,56) and in frail elderly (21,25) there is a diminished capacity for adaptation at these advanced ages. For example, Slivka et al (56) recently demonstrated a complete lack of adaptation to resistance training at the single fiber level in men Ն 80 yr of age.…”
Section: Impact Of Endurance Training On Skeletal Muscle Aerobic Funcmentioning
confidence: 97%
“…Nonetheless, many studies in middle-to late-middle-aged individuals have shown a maintained capacity to increase whole body maximal oxygen uptake (V O 2 max ) (28,42,43) and mitochondrial enzyme activity (14,63) following exercise training relative to young adults. Very few studies have examined whole body aerobic responses to endurance training in very advanced age (Ն80 yr of age; senescence) (20,41), and none has assessed adaptability of the skeletal muscle aerobic machinery specifically. Since improvements in muscle and whole body V O 2 max are accompanied by increases in mitochondrial enzyme activity in both young adult and late-middleaged muscle (9,14,17), it is important to establish the efficacy of endurance training on the skeletal muscle aerobic machinery at these advanced ages because such adaptations are important to whole body aerobic capacity and mobility in the elderly.…”
mentioning
confidence: 99%
“…Improving muscular frailty Muscular frailty is a hallmark of ageing (Runge et al 2004), and training seems to be an appropriate means to counteract, at least partly, the debilitating effects of senescence (Fiatarone et al 1990;Malbut et al 2002;Mian et al 2007).…”
Section: Clinical Applicationmentioning
confidence: 99%